Towards the creation of a searchable 3D smart city model - Nawel Lafioune; Michèle St.-Jacques (Innovation & Management Review, 2020)
Purpose - This paper aims to create a new searchable 3D city model to help managers improve their decision-making. Design/methodology/approach This paper identifies data management basics and the key elements used in the new model design; it further analyzes five-city models, presents its findings and proposes analytical trends for the new model. It discusses the concepts underlying existing models, explains the benefit brought by the proposed model and demonstrates its robustness. Findings City systems can be interconnected, thanks to data digitization and the integration of new technologies into different management processes. Although there are several 3D city models available, none of those identified in this research can be queried for several sectors. Research limitations/implications This model design can only be successfully realized in the presence of a public mandate. Potential limitations include information security risks and political non-acceptance. Originality/value The present work proposes a searchable and high performance model having the distinctive capacity to bring together city systems and perform real-time data analysis in order to extract important information needed to guide the city, and in the context of a global vision.
Keywords: 650; 3D city model; BIM; Blockchain; CIM; Data management; Digital model; IOTA; SIG; Smart city